Effect of intramedullary nail and locking plate in the treatment of proximal humerus fracture: an update systematic review and meta-analysis - Xiaoqing Shi; Hao Liu; Runlin Xing; Wei Mei; Li Zhang; Liang Ding; Zhengquan Huang; Peimin Wang (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background To evaluate the effect of intramedullary nail and locking plate in the treatment of proximal humerus fracture (PHF). Methods China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang database, Chinese Biomedicine Database (CBM), PubMed, EMBASE, Web of Science, and Cochrane Library were searched until July 2018. The eligible references all show that the control group uses locking plates to treat PHF, while the experimental group uses intramedullary nails to do that. Two reviewers independently retrieved and extracted the data. Reviewer Manager 5.3 was used for statistical analysis. Results Thirty-eight retrospective studies were referred in this study which involves 2699 patients. Meta-analysis results show that the intramedullary nails in the treatment of proximal humeral fractures are superior to locking plates in terms of intraoperative blood loss, operative time, fracture healing time, postoperative complications, and postoperative infection. But there is no significance in constant, neck angle, VAS, external rotation, antexion, intorsion pronation, abduction, NEER, osteonecrosis, additional surgery, impingement syndrome, delayed union, screw penetration, and screw back-out. Conclusions The intramedullary nail is superior to locking plate in reducing the total complication, intraoperative blood loss, operative time, postoperative fracture healing time and postoperative humeral head necrosis rate of PHF. Due to the limitations in this meta-analysis, more large-scale, multicenter, and rigorous designed RCTs should be conducted to confirm our findings. Trial registration PROSPERO CRD42019120508